Arabic Language as Representation of Muslim Identity in Indonesia - Yuangga Kurnia Yahya; Umi Mahmudah; Siti Nikmatul Rochma (Lakhomi Journal Scientific Journal of Culture, 2021)
This study is a qualitative research by collecting data from multiple sites that discuss the importance of learning the Arabic language for the people of Indonesia. Top 5 sites with those keywords are Rumaysho.com., BelajarIslam.com, Islampos.com, Kompasiana.com., and kiblat.net. From those five sites will be analyzed with the Yasir Suleiman’s language and religious identity perspective which shows that language has a function as an instrument of communication and also, a symbol of identity. This study found that stereotyping against the Arabic language makes it even more exclusive and closed to non-Muslims in Indonesia. Learning the Arabic language itself is not limited to the religious orientation, but making it as a function of language itself, as a medium of communication. Arabic language has been ‘sacred’ with its strategic position in political, economical, ideological, and academic field.